EFFECT OF GROWTH REGULATORS ON PLANT GROWTH AND CORMEL PRODUCTION OF GLADIOLUS - MANPREET KALSI; K K DHATT; NIRMALJIT KAUR (The Bioscan, 2019)
The present investigation was undertaken in the experimental field area of Floriculture and Landscaping, Punjab Agricultural University, Ludhiana, during 2015-2016. The cormels of four varieties of gladiolus namely CPG, Punjab Glance, Sylvia and Novalux were treated with gibberellic acid (50, 100, 150 and 200 ppm) and benzyladenine (25, 50, 75, 100, 125 ppm) as pre planting dip treatment for 12 hours. The analysis of variance was conducted as per factorial randomized block design. The result revealed various parameters like minimum time to sprouting of cormels was recorded with gibberellic acid 200 ppm and maximum sprouting percent, plant height(cm), leaf length(cm), width(cm), area(cm2), no of leaves/plant, cormels, diameter, weight of cormels was recorded with gibberellic acid 200 ppm followed by BA 125 ppm.